2019
DOI: 10.1038/s41366-019-0450-9
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the C19MC microRNA locus in the placenta: association with maternal and chilhood body size

Abstract: Objectives: To study DNA methylation at the C19MC locus in the placenta and its association with: 1) parental body size, 2) transmission of haplotypes for the C19MC rs55765443 SNP, 3) offspring's body size and/or body composition at birth and in childhood. Subjects and methods: Seventy-two pregnant women-infant pairs and 63 fathers were included in the study. Weight and height of mothers, fathers and newborns were registered during pregnancy or at birth (n=72). Placental DNA methylation at the C19MC imprinting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…In the current study, the expression level of miR520a-3p and miR-520a-3p in fetal cord blood had positive correlations with newborn body weight. These results are also supported by a very recent study that lower levels of the placenta C19MC methylation status was associated with increased maternal pre-pregnancy weight, and with higher weight and fat mass of their offspring [41]. Therefore, it is plausible that declines in C19MC methylation status in the placenta of overweight/obese pregnant women upregulates the expression of C19MC miRNA, which adversely affects the gene expression pattern and phenotype of the fetus.…”
Section: Discussionsupporting
confidence: 71%
“…In the current study, the expression level of miR520a-3p and miR-520a-3p in fetal cord blood had positive correlations with newborn body weight. These results are also supported by a very recent study that lower levels of the placenta C19MC methylation status was associated with increased maternal pre-pregnancy weight, and with higher weight and fat mass of their offspring [41]. Therefore, it is plausible that declines in C19MC methylation status in the placenta of overweight/obese pregnant women upregulates the expression of C19MC miRNA, which adversely affects the gene expression pattern and phenotype of the fetus.…”
Section: Discussionsupporting
confidence: 71%
“…Previously reported imprinted expression of the miRNA cluster located on chromosome 19 (C19MC) [31,32] was also evident in our data. Previous work further linked the amplitude of the imprinting effect with the mother's BMI [48]. Our analysis of demographic variables indicated that the relationship between C19MC cluster imprinting and mother's BMI depends on the mother's weight but not the height.…”
Section: Discussionmentioning
confidence: 55%
“…Previously reported imprinted expression of the miRNA cluster located on chromosome 19 (C19MC) [ 31 , 32 ] was also evident in our data. Previous work further linked the amplitude of the imprinting effect with the mother’s BMI [ 48 ]. Our analysis of demographic variables indicated that the relationship between C19MC cluster imprinting and mother’s BMI depends on the mother’s weight but not the height.…”
Section: Discussionmentioning
confidence: 99%